HLA-E and Its Soluble Form as Indicators of a Sex-Specific Immune Response in Patients with Oral Squamous Cell Carcinoma - Radermacher, Anne; Fehrenz, Michael; Bellin, Tamara; Claßen, Carolina; Möller, Laura; Struckmeier, Ann-Kristin; Wagner, Mathias; Wartenberg, Philipp; Moratin, Julius; Freudlsperger, Christian; Freier, Kolja; Horn, Dominik (International Journal of Molecular Sciences, 2023)
The human leukocyte antigene E (HLA-E) is associated with tumorigenesis in various cancers. Immunoncology along with sex-specific aspects in cancer therapy are now in scientific focus. Therefore, immunohistochemical HLA-E expression was retrospectively analysed in a cohort of oral squamous cell carcinomas (OSCC) after surgical therapy. Then, serum concentration of HLA-E (sHLA-E) was quantified in a prospective cohort by enzyme-linked immunosorbent assay. High HLA-E expression was associated with advanced UICC stage (Spearman’s correlation: p = 0.002) and worse survival (Cox-regression: progression-free survival: hazard ratio (HR) 3.129, confidence range (CI) 1.443–6.787, p = 0.004; overall survival: HR 2.328, CI 1.071–5.060, p = 0.033). The sHLA-E concentration was significantly higher in the control group than in tumor group (Mann–Whitney U-test (MW-U): p = 0.021). Within the tumor group, women showed significantly higher sHLA-E levels than men (MW-U: p = 0.049). A closer look at the tumor group and the control group showed that gender-specific differences exist: while no differences in sHLA-E concentration were detectable between female subjects of tumor group and control group (MW-U: p = 0.916), male subjects of tumor group had a significantly lower sHLA-E concentration compared to those of control group (MW-U: p = 0.001). In summary, our results provide evidence for sex-specific differences in immune responses in OSCC. This fact should be considered regarding future immunotherapy regimens.
CRIS-Team Scopus Importer:2023-12-22
Keywords: HLA-E; immunotherapy; oral squamous cell carcinoma (OSCC); sex-related differences in immune response; soluble HLA-E